Rothman-Simeone and Herkowitz's the spine - Garfin, Steven R; Eismont, Frank J; Bell, Gordon R; Fischgrund, Jeffrey S; Bono, Christopher M (Elsevier, 2018)
Rothman-Simeone and Herkowitz’s The Spine, 7th Edition, presents state-of-the-art techniques, helping you apply today’s newest developments in your practice. Nakladatelská anotace. Kráceno
Keywords: ortopedie; Spine; Spinal Diseases; bolesti zad; Back Pain; mícha; poranění páteře; Spinal Cord; nemoci páteře; Spinal Injuries; páteř